THE INFLUENCE OF COMPENSATION, WORK MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES IN ADMINISTRATIVE DEPARTMENT WITH WORK LOYALTY AS AN INTERVENING VARIABLE AT THE AIRPORT AUTHORITY OFFICE IN MEDAN REGION II - Dodi Hendra Silaen; Muhammad Toyib Daulay; Kiki Farida Ferine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study was to determine the effect of compensation, work motivation and work discipline on the performance of employees in the administrative division with work loyalty as an intervening variable. The research was carried out using associative quantitative research. is 70 and the researcher wants to make all of the population into a sample and uses a saturated sample technique. This research model is used with analysis paths and measuring tools used Smart PLS 3.3.3 data collection used is a questionnaire and survey. The results of this study have a direct influence from the 5 hypotheses and will be explained per hypothesis. Work Discipline has a negative and not significant effect on original sample -0.055 P values 0.642 > 0.05, Work Discipline has a positive and insignificant effect on Work Loyalty Original Sample 0.252 P values 0.